Preparation and Characterization of N, S Co-doped TiO2 Nanopowder and its Photocatalytic Activity under Visible Light - Hu, S.Z.; Li, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2012)
N, S co-doped TiO2 was prepared via a hydrothermal process. X-ray diffraction, UV-VIS spectroscopy and X-ray photoelectron spectroscopy were conducted to characterize the prepared TiO2 particles. The results indicated that N and S doped into the TiO2 crystal lattice simultaneously by hydrothermal process. The photocatalytic performance in the degradation of methylene blue indicated that N and S doped TiO2 showed much higher photocatalytic activity than pure TiO2 under visible light. Co-doping sample exhibited the highest activity. This is probably due to the synergistic effect of reduced particle size, optimal anatase/rutile ratio, reduced electron-hole recombination rate and more absorption in visible light region.